2019
DOI: 10.3390/ijms20215430
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib Inhibits Procoagulant and Clot Retracting Activities of Human Platelets

Abstract: Tyrosine kinase inhibitors (TKI) such as the BCR-ABL inhibitor dasatinib and nilotinib are highly effective therapies for chronic myeloid leukemia (CML). However, several lines of evidence suggest that dasatinib can induce bleeding which may be due to impaired collagen-induced platelet adhesion, aggregation, and secretion. Sarcoma family kinases (SFK) play central role in the GPVI-induced signaling pathway. We aimed to investigate whether and how dasatinib can modulate SFK-mediated platelet procoagulant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…None of the samples had evident fibrin colocalized on the platelet periphery, compared with those in the noncrosslinked clot [Color figure can be viewed at wileyonlinelibrary.com] mFab-F and strongly decreased by dasatinib, a tyrosine kinase inhibitor that strongly inhibits GPVI-induced platelet activation but only weakly inhibits thrombin and ADP-induced platelet activation through the inhibition of outside-in activation by integrin αIIbβ3. 30,31 Furthermore, control platelets show strong colocalization with fibrin(ogen) and integrin αIIbβ3 and the colocalization is decreased by mFab-F and dasatinib. These results suggest that platelets are weakly activated on fibrin and the activation is decreased by inhibition of GPVI binding to fibrin and its activation pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the samples had evident fibrin colocalized on the platelet periphery, compared with those in the noncrosslinked clot [Color figure can be viewed at wileyonlinelibrary.com] mFab-F and strongly decreased by dasatinib, a tyrosine kinase inhibitor that strongly inhibits GPVI-induced platelet activation but only weakly inhibits thrombin and ADP-induced platelet activation through the inhibition of outside-in activation by integrin αIIbβ3. 30,31 Furthermore, control platelets show strong colocalization with fibrin(ogen) and integrin αIIbβ3 and the colocalization is decreased by mFab-F and dasatinib. These results suggest that platelets are weakly activated on fibrin and the activation is decreased by inhibition of GPVI binding to fibrin and its activation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the interaction of resting platelets with fibrin clots, we allowed resting platelets to adhere to the fibrin clot and observed the morphology of the adhered platelets and fibrin (Figure 8). Control platelets bound to noncrosslinked fibrin showed that some platelets are spread, whereas spreading is slightly decreased by mFab‐F and strongly decreased by dasatinib, a tyrosine kinase inhibitor that strongly inhibits GPVI‐induced platelet activation but only weakly inhibits thrombin and ADP‐induced platelet activation through the inhibition of outside‐in activation by integrin αIIbβ3 30,31 . Furthermore, control platelets show strong colocalization with fibrin(ogen) and integrin αIIbβ3 and the colocalization is decreased by mFab‐F and dasatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dasatinib can block GPVI-mediated platelet responses (254). Taken together, these findings suggest dasatinib has been a good candidate for blocking SFK downstream activation (255).…”
Section: Effect Of Src Family Kinase Inhibitor (Dasatinib) On Platele...mentioning
confidence: 81%
“…The mechanism of action has not been clarified, but cross talk between GPCR signaling and αIIbβ3 can be suggested. In both probands and patients with chronic myeloid leukemia, treatment with dasatinib, a multikinase inhibitor, inhibits convulsin-induced phosphatidylserine exposure, αIIbβ3-activation, thrombin formation, clot retraction, and thrombus volume [18]. As the mechanism, the inhibition of collagen signaling via the inhibition of Src, known to be involved in outside-in signaling, caused by an off-target effect of dasatinib, has been demonstrated.…”
Section: Pharmakons Affecting Clot Retraction In Humansmentioning
confidence: 99%